Formulasi Self Nano Emulsifying Drug Delivery System (SNEDDS) Minyak Biji Jinten Hitam dengan Surfaktan Tween 80 dan Kosurfaktan Sorbitol - Iis Wahyuningsih; Yenni Latief (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Black cumin seed oil has many benefits. One of which is as an anticancer, it can be used as an opportunity to develop drugs that utilizes the black cumin seed oil. A method to improve the stability and absorption of the drug in the body is within the formulation of Self Nano Emulsifying Drug Delivery System (SNEDDS). This study aims to determine whether the black cumin seed oil can be made into SNEDDS formula with tween 80 and sorbitol as a surfactant and cosurfactant along with the establishment for the optimal formula. SNEDDS formula of black cumin seed oil was optimized using SLD method by DX.10 software. SNEDDS formula was made using tween 80 as surfactant and sorbitol as cosurfactant. Previously carried out with the manufacturing of a trial formula to determine the lower and upper value of each component, then 14 formulas were made based on DX.10. The formula were evaluated for transmittance percentage in 650 nm wavelength and emulsification time of 37oC. Results of the tests included in DX10 is to obtain the optimal formula. The optimal formula was validated by t-test and evaluated for droplet size, zeta potential, and stability test of nanoemulsion in artificial gastric fluid (AGF) and artificial intestinal fluid (AIF) for 4 hours. The results showed that the proportion of 13% black cumin seed oil, 60% tween 80 and 27% sorbitol is able to establish the optimal SNEDDS formula of black cumin seed oil. Transmittan value of the optimal formula was 92% with the emulsification time of 56 seconds, SNEDDS black cumin seed oil droplet size of 21.5 nm, zeta potential value -31.5 mV and nanoemulsion stable in the AIF and AGF.